Pharm-Care Tadulako®: Web-Based Design Application to Improve Pharmaceutical Care Services - Rumi, Amelia; Faisal, Muhammad; Syarifuddin, Nuryani; Purwanti, Rani; Natasya, Putri; Serli, Serli; Yusriadi, Yusriadi; A. Khairinisa, Miski (Universitas Padjadjaran, Indonesia, 2023)
Pharmaceutical services recently require new ideas and innovation to provide maximum benefit concerning the pharmacological treatments of patients and taking responsibility for the process of monitoring their therapy. One of the efforts proposed to be implemented by pharmacists is the pharmaceutical care program which is designed to ensure pharmacists are able to monitor safe and effective medication use and also to provide timely access to medicines for the population. Moreover, the application of eHealth in terms of technology is expected to be effective, networked, patient-centered, and accessible for patients. Therefore, Pharm-Care Tadulako® which is a personalized eHealth application designed with key features of pharmaceutical care to enhance communication between pharmacists and patients is presented in this study. Some of the services designed to be provided by this application include electronic medical records, drug reminders, pharmaceutical messenger, clinical data monitoring, and medication analysis. The application was designed using Software Development Life Cycle (SDLC) Waterfall, after which a pilot study was conducted at four pharmacies in Palu City, Centre of Sulawesi, Indonesia, using 30 patients who volunteered willingly to participate in the experiment. It was discovered that 65% out of the 30 patients were aged 26-45 years old out of which 36% were observed to be suffering from hypertension. The Pharm-Care Tadulako® application was found to have a good impact on pharmacists during the process of providing pharmaceutical care services to patients while they were able to monitor their treatment through the five main features of the application.